2004
DOI: 10.1161/01.cir.0000136582.33493.cc
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Arterial Stiffness and Subclinical Aortic Atherosclerosis

Abstract: Background-Noninvasive measures of arterial compliance may be useful for the detection of subclinical atherosclerosis. Methods and Results-Measures of calf and thigh arterial compliance (MaxV50) were recorded in 267 subjects who also underwent MRI of the distal aorta to quantify distal aorta atherosclerosis. The average of calf and thigh MaxV50 was strongly predictive of extent of aortic atherosclerosis and risk of being in the top quartile of aortic atherosclerosis after adjustment for the Framingham Coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 43 publications
(23 reference statements)
3
31
0
Order By: Relevance
“…Mounting evidence show that sleep apnoea enhances endothelial dysfunction and arterial stiffness, the key factors in the development of atherosclerosis [10][11][12][24][25][26]. The prevalence of sleep apnoea in our PAD patients is higher than in any other previously reported population with manifestations of atherosclerosis, with earlier studies showing 30-58% prevalence of OSA in coronary artery disease and 30-80% prevalence in arterial hypertension [3,4,8].…”
Section: Discussionsupporting
confidence: 40%
“…Mounting evidence show that sleep apnoea enhances endothelial dysfunction and arterial stiffness, the key factors in the development of atherosclerosis [10][11][12][24][25][26]. The prevalence of sleep apnoea in our PAD patients is higher than in any other previously reported population with manifestations of atherosclerosis, with earlier studies showing 30-58% prevalence of OSA in coronary artery disease and 30-80% prevalence in arterial hypertension [3,4,8].…”
Section: Discussionsupporting
confidence: 40%
“…Herrington et al 22 demonstrated that a measure of lower extremity arterial stiffness was associated with aortic atherosclerotic burden quantified by MRI. In a study of Ͼ3000 elderly subjects aged 60 to 101 years, aPWV was related to the extent of atherosclerotic plaque in the aorta and the carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] The progressive deterioration of conduit vessel function may be the common pathway of multiple risk factors that lead to similar clinical end points (ie, left ventricular hypertrophy, myocardial infarction, congestive heart failure, atherosclerosis, and death). 40,41 Patients with wide PP may be predisposed to acute postoperative renal dysfunction because of occult abnormal vascular *Among the 2381 patients in the derivation cohort, 47 patients were excluded with missing values for at least 1 of the predictors in the model, including the covariates. The Hosmer-Lemeshow goodness-of-fit 2 test statistic was 5.5 (Pϭ0.599).…”
Section: Pp Hypertensionmentioning
confidence: 99%
“…44,45 In addition, pulsatile stress in central arteries may contribute to plaque rupture by a mechanical fatiguing effect. 40 PP, necessarily increased in patients with isolated systolic hypertension, can be singled out as a greater predictor of risk for stroke, heart failure, coronary artery disease, and renal failure than diastolic blood pressure. 3,46,47 This study showed a significant and progressive increase in the risk of renal composite above a PP threshold of 40 mm Hg.…”
Section: Pp Hypertensionmentioning
confidence: 99%